Analysis of design elements on soda drink packaging in influencing youth consumer purchase decision - Alias, Siti Sharina; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
The development of the Fast-Moving Consumer Goods (FMCG) sector shows a high upward trend and is growing rapidly. There are many brands of products for this sector in the market and it creates a great competition. Young generations are seen as target consumers who contribute to this sector. Packaging design is one of the important elements that contribute to an effective marketing strategy. Therefore, this study which focuses on soda drinks was conducted to analyse what elements of design are most effective in influencing the decision of young consumers in the decision to buy soda drinks. The data was collected using content analysis and questionnaire surveys. The analysis shows that youth consumers are very influenced with the elements of design that are used for the design of cans or bottles of soda drinks. The colour and imagery are two important elements that influence the decision of youth consumers to purchase soda drinks. The result of this study provides important insight to soda drink product brands concerning the need to adopt appropriate elements of design for their packaging designs that target young consumers.